New training method approach on perception-awareness to improve sport performance on volleyball athletes - D`Isanto, T.; Karçurri, A.; Kasa, A.; Di Lascio, G.; D`Elia, F. (International Journal of Kinesiology & Sports Science, 2025)
Background: Jumping ability in volleyball is a key determinant of athletic performance. While different studies focus on methods to enhance vertical jump, few address athletes` perception and awareness in conjunction with performance metrics.